A more advanced theoretical model of the sphere earth’s EM in a foreign homogeneous EM field - Bjelić, Slobodan N.; Marković, Nenad A. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The paper describes a more advanced theoretical model of the Earth’s EM field based on two-component hypotheses. A defined mathematical model shows the rotation of the magnetically conducting sphere of the magnetization M in a foreign magnetic field and the components of the magnetic field that may arise due to the rotation of the Earth around its axis. According to the established model, in relation to the reference values of the planet Earth, the values of the components of the other planets in the solar system were calculated and the results were tabulated. Methods: The solution to the problem highlighted in the title of the paper was determined using the combined, for that purpose, formalized methods of physics and mathematical analysis, in order to develop a new, more advanced mathematical model. For this purpose, the method of analogy was used, related to the application of similar structural forms and systems for researching electromagnetic processes and planetary rotation. The method of analogy was applied for two interrelated reasons. The first one is that all values that characterize the function of any natural system are subject to change, and the second one is that the applied solutions do not determine the conditions of the structure’s function in each specific case. Results: The solutions in the form of original analytical formulas and numerical values arranged in Table 2, referring to the influence of the rotation of the planets and especially the Earth, will be applied to research the effects of the EM field emitted by the Sun towards the planets, especially the role that the process plays in protecting the planet Earth. The results given in Table 2 are particularly important. Conclusion: The paper discusses the appearance and effect of the Earth’s EM field in a way that is understandable at the current level of scientific development. Scientific findings in science and measurements in geo- and astrophysics indicate the Sun as a possible source of the EM field that extends through interplanetary space and the component of the Earth’s magnetic field is only a response to the influence of that source. Natural phenomena and processes on the Earth can be defined in system theory by a model that contains changes in the parameters of the state of the planet.